PERAN LEMBAGA KEUANGAN MIKRO DALAM PEMBERDAYAAN EKONOMI MASYARAKAT KECIL MENENGAH - Esty Pudyastuti; Hasrul Siregar; Martin Luter Purba; Wisnu Yusditara; Hendrik E.S. Samosir (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to determine the role of microfinance institutions in empowering the small and medium-sized communities. SMEs really need the role of microfinance institutions, especially in terms of funds to expand markets and develop their businesses, so as to make a large contribution to the national economy. The role of MFIs has been tested, survived the economic crisis and even strengthened. MSMEs are business units where the Indonesian economy has so far relied heavily on MFIs. It is not surprising that many parties have turned their attention to MFIs, but the attention given has not fully touched the face of MFIs with fundamental questions. microfinance institutions so that they can actually strengthen and develop as micro, small and medium enterprises, especially financial institutions in small communities. This microfinance institution was established because it was driven by the community's need for funds to develop their business. the question about the need for funds faced by the majority of the community has been responded positively by several people who are willing to lend some of their funds for MSME capital. Funds lent to customers come from the MFI's own funds or from depositing funds into the microfinance fund of the client's institution. Judging from the potential and funding sources that have been implemented, the MFI actually serves customers and manages them based on. If financial institutions can coordinate fund management with each other, then this can be a huge advantage